Питание клеща Tetranychus cinnabarinus Bоisduval нехарактерным кормовым растением - Барабанова, В.А. (Вестник зоологии, 1977)
The state of Tetranychus cinnabarinus and level of their digestive enzymes were-studied when feeding on bean and maize leaves. Maize nutrition for a long time (2-3 generations) resulted in the mite gradual degeneration, decrease in three number, drop of-protein content in a body as well as in a decrease of digestive enzymes activity, which. confirms that maize leaf has either biochemical composition unsuitable for nutrition of the given mite species or it lacks certain components without which the mites cannot live for a long time.